2022
DOI: 10.1155/2022/1864776
|View full text |Cite
|
Sign up to set email alerts
|

NUTRIC Score Is Not Superior to mNUTRIC Score in Prediction of Mortality of COVID-19 Patients

Abstract: Objectives. The NUTRIC (nutrition risk in the critically ill) score and the modified NUTRIC score are two scoring systems that show the nutritional risk status and severity of acute disease of patients. The only difference between them is the examination of interleukin-6 (IL-6) level. The aim of this study was to investigate whether or not the NUTRIC score is superior to the mNUTRIC score in the prediction of mortality of patients with COVID-19 followed up in the Intensive Care Unit (ICU). Material and Method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The consistent findings of elevated inflammatory markers (such as IL-6 and procalcitonin) and impaired nutritional markers (such as albumin) in patients with high mNUTRIC scores across different studies highlight the importance of these biomarkers in assessing the nutritional status and disease severity of critically ill patients. These findings provide valuable insights into the potential use of these markers in risk stratification and clinical management in the context of critical care [17].…”
Section: Discussionmentioning
confidence: 90%
“…The consistent findings of elevated inflammatory markers (such as IL-6 and procalcitonin) and impaired nutritional markers (such as albumin) in patients with high mNUTRIC scores across different studies highlight the importance of these biomarkers in assessing the nutritional status and disease severity of critically ill patients. These findings provide valuable insights into the potential use of these markers in risk stratification and clinical management in the context of critical care [17].…”
Section: Discussionmentioning
confidence: 90%
“…We reviewed the literature and found that the mNUTRIC score was not superior to the APACHE II score in predicting prognosis in patients with sepsis [43]. Similarly, in a study to predict the prognosis of coronavirus disease 2019 patients, the APACHE score and SOFA score also performed better than the mNUTRIC score [44]. However, we cannot deny the important role of the mNUTRIC score, as it is not only a prognostic indicator, but also a tool for nutritional risk assessment.…”
Section: Discussionmentioning
confidence: 93%
“…Third, the measurement of IL-6 was not available in our study population, and we were unable to calculate the NUTRIC score. Fortunately, many studies have shown that the mNUTRIC score is non-inferior to the NUTRIC score [ 21 , 32 , 33 ]. As this is one of the first studies suggesting the substitution of APACHE II with SAPS II, more multinational studies are required to validate these results and incorporate them into clinical practice.…”
Section: Discussionmentioning
confidence: 99%